2015
DOI: 10.1002/jssc.201500083
|View full text |Cite
|
Sign up to set email alerts
|

Speciation analysis of mercury in sediments using ionic‐liquid‐based vortex‐assisted liquid–liquid microextraction combined with high‐performance liquid chromatography and cold vapor atomic fluorescence spectrometry

Abstract: An improved novel method based on ionic liquid vortex-assisted liquid-liquid microextraction has been developed for the extraction of methylmercury, ethylmercury and inorganic mercury in sediment samples prior to analysis by high-performance liquid chromatography with cold vapor atomic fluorescence spectrometry. In this work, mercury species were firstly complexed with dithizone, and the complexes were extracted into 1-hexyl-3-methylimidazolium hexafluorophosphate. Key factors that affect the extraction effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Following water samples, the most frequently analyzed material for mercury was seafood samples, such as fish, shrimp, and seaweed. A few studies reported the determination of mercury in various environmental samples, such as petroleum hydrocarbons [ 88 ], human hair [ 89 , 90 ], phosphate fertilizers [ 53 ], glycerin [ 91 ], sediments [ 55 , 92 , 93 ], cosmetics [ 94 ], living cells [ 66 , 95 ], and tobacco [ 67 ]. However, a few methods [ 74 , 81 , 87 , 96 101 ] did not report their applicability to natural samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following water samples, the most frequently analyzed material for mercury was seafood samples, such as fish, shrimp, and seaweed. A few studies reported the determination of mercury in various environmental samples, such as petroleum hydrocarbons [ 88 ], human hair [ 89 , 90 ], phosphate fertilizers [ 53 ], glycerin [ 91 ], sediments [ 55 , 92 , 93 ], cosmetics [ 94 ], living cells [ 66 , 95 ], and tobacco [ 67 ]. However, a few methods [ 74 , 81 , 87 , 96 101 ] did not report their applicability to natural samples.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, electrochemical methods had a higher degree of selectivity and did not suffer from interference from other ions. Determination of the level of interference was not performed by a large number of authors [ 45 47 , 53 , 55 , 59 , 60 , 62 , 63 , 69 , 88 , 91 , 92 , 102 106 ] who determined mercury with spectrometric instruments. However, those using electrochemical instruments, spectrophotometers, or spectrofluorometers largely reported the level of interfering ion(s).…”
Section: Discussionmentioning
confidence: 99%
“…The most comprehensive of these (102 references with titles) covers the measurement of mercury species in sediments and soils by HPLC-ICP-MS. 142 The extraction protocols covered are categorised as: acid-base extraction, water distillation, organic solvents and those employing sulydryl containing reagents and a brief discussion of the use of each of these reagent classes is given. 144 Three ILs in combination with three chelating reagents were investigated and the optimal combination was found to be chelation of the Hg species with dithizone (DTZ) and extraction into 1-hexyl-3-methylimidazolium hexauorophosphate ([C 6 MIM][PF 6 ]). The authors recommend that distillation should be the preferred extraction method despite the known problems of potential MeHg formation, from iHg present in the sample, using this technique.…”
Section: Mercurymentioning
confidence: 99%
“…It is therefore necessary to establish sensitive and rapid methods for detecting plasticizer contamination in food and packaging materials. Phthalate plasticizers are generally detected by gas chromatography (GC), high-performance liquid chromatography (HPLC), gas chromatography-mass spectrometry (GC-MS), and liquid chromatography-mass spectrometry (LC-MS) (Leng, Chen, & Wang, 2015;Sendón et al, 2012). Although GC and LC are widely used, they are susceptible to interference by complex substrates, and they have the disadvantages of low sensitivity and long operating times.…”
Section: Introductionmentioning
confidence: 99%